2012
DOI: 10.1002/sia.4926
|View full text |Cite
|
Sign up to set email alerts
|

Surface sputtering with nanoclusters: the relevant parameters

Abstract: In this contribution, we compare the results of our recent molecular dynamics simulations with data already published by us and by other authors to identify the relevant physical parameters governing observables such as the range, the damaged volume, the crater shape, the sputtering yield, the emission of molecules and fragments, and the chemical reactions induced in organic solids by cluster projectiles. Among the considered physical quantities, we show for instance that the total cluster energy, the energy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…From the discussion earlier, it became clear that the damage is reduced when sputtering with low E / n . On the other hand, it has been reported that sputtering yields strongly decrease with decreasing energy/atom. Our experimental data presented in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…From the discussion earlier, it became clear that the damage is reduced when sputtering with low E / n . On the other hand, it has been reported that sputtering yields strongly decrease with decreasing energy/atom. Our experimental data presented in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The energy per projectile mass (i.e., substantially velocity) is known to be one of the physical parameters affecting the sputtering process and thus the sputtering yields [19][20][21]. The molecular clusters used in this experiment have the same cluster size and total energy (5 keV), but have different masses due to the different masses of the constituent molecules, and therefore different E/m.…”
Section: Resultsmentioning
confidence: 99%
“…Delcorte et al . have explored in some detail the sputter yield and fragmentation of molecular species as a function of E/nucleon from large cluster impacts . This work suggests a mechanistic change at an E/nucleon of about 1 eV.…”
Section: Resultsmentioning
confidence: 99%